2018
DOI: 10.1038/s41467-018-05916-9
|View full text |Cite
|
Sign up to set email alerts
|

Luciferase-induced photoreductive uncaging of small-molecule effectors

Abstract: Bioluminescence resonance energy transfer (BRET) is extensively used to study dynamic systems and has been utilized in sensors for studying protein proximity, metabolites, and drug concentrations. Herein, we demonstrate that BRET can activate a ruthenium-based photocatalyst which performs bioorthogonal reactions. BRET from luciferase to the ruthenium photocatalyst is used to uncage effector molecules with up to 64 turnovers of the catalyst, achieving concentrations >0.6 μM effector with 10 nM luciferase constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…BRET has been utilized to control neuronal activity, gene expression, and a photo‐switchable fluorescent protein . A BRET‐induced chemical reaction can also be used to change the function of bioactive molecules, and we reported a BRET‐induced ruthenium‐photocatalyzed reaction . While these precedents highlight novel applications, the extension of the scope of the chemistry that can be performed with bioluminescence is empowering.…”
Section: Figurementioning
confidence: 95%
“…BRET has been utilized to control neuronal activity, gene expression, and a photo‐switchable fluorescent protein . A BRET‐induced chemical reaction can also be used to change the function of bioactive molecules, and we reported a BRET‐induced ruthenium‐photocatalyzed reaction . While these precedents highlight novel applications, the extension of the scope of the chemistry that can be performed with bioluminescence is empowering.…”
Section: Figurementioning
confidence: 95%
“…The precise designo faluciferase-based indicator of drugs (LUCID), involving aS NAP protein, the luciferase and a receptor protein that binds the caged drug, is keyf or the success of the strategy,s ince the luciferase, ruthenium complex and the caged molecule need to be in close proximity. [133]…”
Section: Photoreductive Uncagingmentioning
confidence: 99%
“…In parallel work, we have shown that ab ioluminescence resonancee nergy transfer (BRET) can be used to photoexcite the ruthenium and enable catalysis (Figure 10 D). [70] BRET from luciferase to the ruthenium photocatalyst was used to uncage different effector molecules (drugs or af luorophore) with up to 64 turnoverso ft he catalyst, achieving concentrations > 0.6 mm effector with 10 nm luciferase construct. Using aB RET sensor, we furtherd emonstrated that this catalysis could be modulated in response to an analyte, analogous to an allosterically controlled enzyme.…”
Section: Cross-couplingr Eactions In the Presence Of Biomoleculesmentioning
confidence: 99%